2015
DOI: 10.1073/pnas.1513609112
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of CCA1 targets uncovers an expanded clock network inArabidopsis

Abstract: The circadian clock in Arabidopsis exerts a critical role in timing multiple biological processes and stress responses through the regulation of up to 80% of the transcriptome. As a key component of the clock, the Myb-like transcription factor CIRCADIAN CLOCK ASSOCIATED1 (CCA1) is able to initiate and set the phase of clockcontrolled rhythms and has been shown to regulate gene expression by binding directly to the evening element (EE) motif found in target gene promoters. However, the precise molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
279
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(308 citation statements)
references
References 71 publications
17
279
1
3
Order By: Relevance
“…1). At dawn, two MYB transcription factors, CIRCADIAN CLOCK ASSOCIATED1 (CCA1) and LATE ELONGATED HYPOCOTYL (LHY), repress evening-phased genes (Nagel et al, 2015;Kamioka et al, 2016). This repression is partly dependent on the function of the CONSTITUTIVE PHOTOMORPHOGENIC10 (COP10)-DE-ETIOLATED1-DAMAGED DNA BINDING1 complex, a negative regulator for photomorphogenesis (Lau et al, 2011).…”
Section: A Molecular Framework Of the Circadian Oscillatormentioning
confidence: 99%
See 1 more Smart Citation
“…1). At dawn, two MYB transcription factors, CIRCADIAN CLOCK ASSOCIATED1 (CCA1) and LATE ELONGATED HYPOCOTYL (LHY), repress evening-phased genes (Nagel et al, 2015;Kamioka et al, 2016). This repression is partly dependent on the function of the CONSTITUTIVE PHOTOMORPHOGENIC10 (COP10)-DE-ETIOLATED1-DAMAGED DNA BINDING1 complex, a negative regulator for photomorphogenesis (Lau et al, 2011).…”
Section: A Molecular Framework Of the Circadian Oscillatormentioning
confidence: 99%
“…Chromatin immunoprecipitation sequencing analyses brought us, to our knowledge, a new insight regarding potential variation in CCA1 binding sites. In addition to Evening Element and the CCA1 Binding Site, DNA motifs that contain G-box or CT repeats are significantly enriched in the CCA1 binding regions (Nagel et al, 2015;Kamioka et al, 2016), indicating that CCA1 may form complexes with different transcription factors that alter the DNA binding preferences of complexes that contain CCA1. Previously, genetic results implied that CCA1 and LHY directly act as transcriptional activators for the morningphased genes PSEUDO RESPONSE REGULATOR9 (PRR9) and PRR7 (Farré et al, 2005).…”
Section: A Molecular Framework Of the Circadian Oscillatormentioning
confidence: 99%
“…In addition, levels of both COR27 and COR28 were also regulated by the clock, both peaking in abundance in the afternoon (ZT15) in LD conditions ( Figure 5B). Given that there are EE (AAAATATCT) and EE-like elements (AATATCT) in the COR27 promoter region (Mikkelsen and Thomashow, 2009) and that it was reported that the promoter of COR27 was occupied by CCA1 in a ChIP-seq analysis of plants expressing CCA1-GFP (Nagel et al, 2015), we measured transcription of COR27 and COR28 in the cca1 lhy double mutant. ACTIN7 (ACT7), ASPARTIC PROTEINASE A1 (APA1), and ISOPENTENYL PYROPHOSPHATE: DIMETHYLALLYL PYROPHOSPHATEISOMETASE2 (IPP2) (Endo et al, 2014) were used as internal controls for normalization in our qPCR analysis.…”
Section: Mutation Of Cor27 and Cor28 Enhances Freezing Tolerancementioning
confidence: 99%
“…In turn, the expression of EC genes and formation of the EC itself are also tightly regulated by the circadian clock through multiple regulatory mechanisms (Herrero et al, 2012;Choudhary et al, 2015). The ELF3, ELF4, and LUX promoters are bound by the key clock protein CCA1, a morning phased myb transcription factor that acts together with its paralog LATE ELONGATED HYPOCOTYL (LHY) to repress evening-phased genes during the day (Lu et al, 2012;Adams et al, 2015;Nagel et al, 2015;Kamioka et al, 2016). Autoregulation of the EC may also be achieved through binding of the LUX protein to its own promoter .…”
mentioning
confidence: 99%